1992
DOI: 10.1111/j.1469-7610.1992.tb01963.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time and Movement Time in Children with a Developmental Coordination Disorder

Abstract: The Test of Motor Impairment (TOMI) was used to select 12 children with a Developmental Coordination Disorder (DCD) and 12 age-matched controls. In an aiming task, movement latency, movement duration and its variability were significantly prolonged in the DCD group. In a coincidence timing version of the task, absolute timing error was significantly greater in the DCD group. The most robust chronometric effect for differentiating the two groups seemed to be the duration of movement when the target was small. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 18 publications
6
28
0
4
Order By: Relevance
“…He also had substantial difficulties in organizing his desk, homework, and space on a page. Impairment in the performance of motor skills, and visual‐spatial skills were completed with the Movement Assessment Battery for Children 2nd edition (Henderson, Rose, & Henderson, 1992), and DTVP2 systematically showing very weak scores (far below the 5th percentile) for the proposed tasks (Table 1). According to the ASHA technical report, deficits in motor learning and motor coordination in the fine and gross motor domains are seen in many children with childhood apraxia of speech, providing further evidence for this diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…He also had substantial difficulties in organizing his desk, homework, and space on a page. Impairment in the performance of motor skills, and visual‐spatial skills were completed with the Movement Assessment Battery for Children 2nd edition (Henderson, Rose, & Henderson, 1992), and DTVP2 systematically showing very weak scores (far below the 5th percentile) for the proposed tasks (Table 1). According to the ASHA technical report, deficits in motor learning and motor coordination in the fine and gross motor domains are seen in many children with childhood apraxia of speech, providing further evidence for this diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reporting slower inhibition performance in children with DCD often observe longer reaction times on trials in which the inhibition of a response is not required (e.g., Go trials on the Go-NoGo task; Querne et al, 2008), and other studies of simple reaction time have reported prolonged latency in children with DCD (Henderson, Rose, & Henderson, 1992;Piek & Skinner, 1999). This may indicate a processing speed deficit, suggesting that longer completion times on RI tasks reflect general inability to process information at an adequate speed, rather than inhibition impairments.…”
Section: Abstract: Response Inhibition Processing Speed Motor Diffimentioning
confidence: 99%
“…Given the heterogeneity and day-to-day variability [28][29][30] of symptoms in DCD, a single case methodology was chosen with several forms of experimental control 31 to increase the internal validity of the study (Figure 1). To control for 'spontaneous' improvement, the length of the baseline condition was randomized per child to between 12 and 18 weeks.…”
Section: Designmentioning
confidence: 99%